2017
DOI: 10.1016/j.clnu.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, body composition, and quality of life in community-dwelling sarcopenic and non-sarcopenic older adults: A case-control study

Abstract: In non-malnourished older adults with and without sarcopenia, we observed that sarcopenia substantially impacted self-reported quality of life and physical activity levels. Differences in nutrient concentrations and dietary intakes were identified, which might be related to the differences in muscle mass, strength and function between the two groups. This study provides information to help strengthen the characterization of this geriatric syndrome sarcopenia and indicates potential target areas for nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
210
1
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(241 citation statements)
references
References 31 publications
13
210
1
17
Order By: Relevance
“…We demonstrate that both aging and frailty associate with higher levels of MMA indicative of a higher prevalence of vitamin B12 deficiency in the Singapore Longitudinal Aging Study. A similar association was also recently demonstrated in a different human population with mobility deficits where sarcopenic patients had lower levels of circulating vitamin B12 compared with age‐matched elderly controls . Taken together, these observations strongly suggest that vitamin B12 deficiency could directly impact muscle performance and physical function in the elderly.…”
Section: Discussionsupporting
confidence: 83%
“…We demonstrate that both aging and frailty associate with higher levels of MMA indicative of a higher prevalence of vitamin B12 deficiency in the Singapore Longitudinal Aging Study. A similar association was also recently demonstrated in a different human population with mobility deficits where sarcopenic patients had lower levels of circulating vitamin B12 compared with age‐matched elderly controls . Taken together, these observations strongly suggest that vitamin B12 deficiency could directly impact muscle performance and physical function in the elderly.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, we observed no effect on plasma homocystein levels after reduced nutritional intake of vitamins B6/B12/folate, indicating that mice were not deficient. However, an age‐related increase in plasma homocystein was observed, which indicates that vitamin B metabolism is already affected by ageing per se . Similarly, GSH levels decreased with advanced age, indicative of increased systemic oxidative stress with ageing.…”
Section: Discussionmentioning
confidence: 97%
“…Huo et al reported that the number of selfreported falls was higher in sarcopenic obese older adults than either sarcopenic or obese alone groups. 34,35 Both ageing and obesity can result in disability by leading to decreased organ function, increased chronic diseases and inflammation. 32 The present study demonstrated that the mean scores for domains of the SF-36 questionnaire were lower in both obese and sarcopenic obese participants compared to the sarcopenic and non-sarcopenic non-obese participants.…”
Section: Discussionmentioning
confidence: 99%